PERILAKU MAHASISWA PENDIDIKAN SOSIOLOGI UNIMA KETIKA PEMBELAJARAN ONLINE DAN SETELAH PENGINPUTAN NILAI - Mesra, Romi; Waldi, Atri; Wijaya, Wibi; Melia, Yenni (Jurnal Ilmiah Mandala Education (JIME), 2022)
There are symptoms of student negligence where they do not pay attention or are negligent in carrying out the directions that have been explained by the lecturer at the beginning so that when the scores that come out are not in line with the student's expectations, they try to ask the lecturers why their scores are like that or how to get better grades. In this study, the researcher will use a qualitative research approach. Based on the results of observations and interviews that have been carried out by researchers, the results of this study were found as follows; Student behavior when learning online: students who actively follow the direction of the lecturer, students who are indifferent to the direction of the lecturer, students who always turn off the video during lectures via the zoom application, students who always turn on the video when lectures through the zoom application, students who carry out other activities when lectures pass zoom application, students who always have many excuses when they are late or do not attend lecture meetings. Student behavior after inputting grades: thanking the lecturer for good grades, questioning the grades given by the lecturer, asking for time to improve grades, asking the lecturer to change the grades, giving reasons for the lack of grades.